2017
DOI: 10.1111/obes.12218
|View full text |Cite
|
Sign up to set email alerts
|

TIPS and the VIX: Spillovers from Financial Panic to Breakeven Inflation in an Automated, Nonlinear Modeling Framework

Abstract: This paper examines the determinants of the breakeven inflation rate (BEI) on U.S. Treasury Inflation Protected Securities. After controlling for several measures of liquidity, inflation expectations and inflation uncertainty; financial fear itself (proxied with the Volatility Index or VIX) remains a primary influence on BEI. To delve into the mechanism underlying this association, the VIX is decomposed, using intraday data, into conditional variance and the variance premium capturing risk aversion. Aside from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The properties of the Autometrics algorithm are detailed extensively in Doornik (2009). 11 While Gets was initially employed in macroeconomics, a growing number of recent studies have applied it to a financial market setting: Sucarrat and Escribano (2012), Bekaert et al (2012), Bekaert and Hoerova (2014), Stillwagon (2016), Stillwagon (2017), Frydman and Stillwagon (2018), Frydman et al (2020), Bekaert and Mehl (2019), and Bonnier (2022). 12 Particularly important are the recent extensions to the Gets methodology, such as impulse indicator saturation (IIS) and step indicator saturation (SIS).…”
Section: General-to-specific Modeling and Autometricsmentioning
confidence: 99%
“…The properties of the Autometrics algorithm are detailed extensively in Doornik (2009). 11 While Gets was initially employed in macroeconomics, a growing number of recent studies have applied it to a financial market setting: Sucarrat and Escribano (2012), Bekaert et al (2012), Bekaert and Hoerova (2014), Stillwagon (2016), Stillwagon (2017), Frydman and Stillwagon (2018), Frydman et al (2020), Bekaert and Mehl (2019), and Bonnier (2022). 12 Particularly important are the recent extensions to the Gets methodology, such as impulse indicator saturation (IIS) and step indicator saturation (SIS).…”
Section: General-to-specific Modeling and Autometricsmentioning
confidence: 99%
“…This result implies that heightened economic pessimism leads to a stronger preference for shorter-term assets and, consequently, an increase in the premium for longer-term assets. In a later study Stillwagon (2018) reported that the difference between conventional Treasury rates and rates on Treasury Inflation Protected Securities (TIPS) correlates negatively with the level of panic measured by the VIX.…”
Section: Introductionmentioning
confidence: 99%